Pemberdayaan UMKM Melalui Penguatan Branding Produk pada Cakwe Cigombong untuk Meningkatkan Daya Saing Melalui Promosi Visual dan Pembayaran Digital - Hansen Hansen; Fatimah Azzahra Auliyani; Eugene Tjoa Putra; Jodista Patricia; Ghaida Zhabira; Marsyal Ananda; Gianina Benedicta; Santi Rimadias (Lembaga Pengembangan Kinerja Dosen, 2024)
Cakwe Cigombong, a micro business located on Jalan Cibogo, Kelapa Dua District, Tangerang Regency, Banten, faces challenges in improving its branding to attract a wider consumer base. An effective branding strategy is very important to support the growth and competitiveness of these MSMEs. This community service activity aims to design and implement branding improvements that are tailored to business needs and conditions. The interventions carried out include the creation and installation of promotional banners, the development of more attractive menu designs, and the integration of the QRIS digital payment system to facilitate transactions. The results show that these efforts increase the attractiveness of the product among consumers. By adopting this branding strategy, Cakwe Cigombong is in a better position to compete and grow in the local market.